Viral diseases in Vigna species - Impacts, management opportunities and future perspectives: A review - Godwin, P; Shoba, D; Arumugam, P M; Saravanan, S; Sheela, J; Kavitha, P A; Arumugachamy, S; Hepziba, J (Plant Science Today, 2025)
Pulses are the second-largest class of food crops worldwide, with around 1.58 million hectares under cultivation. represent. They are also excellent sources of protein. The major cultivated Vigna species in India include Blackgram [Vigna mungo (L.) Hepper], Greengram [Vigna radiata (L.) Wilczek], Cowpea [Vigna unguiculata (L.) Walp.], Moth bean [Vigna aconitifolia (Jacq.) Maréchal] and Adzuki bean [Vigna angularis (Willd.) Ohwi & H. Ohashi]. However, the yield of these crops is significantly reduced by viral diseases caused by a diverse range of viral strains. Notable viral diseases affecting Vigna species include yellow mosaic, cowpea severe mosaic, cowpea yellow mosaic, cowpea aphid-borne mosaic, cowpea golden yellow mosaic, bean common mosaic, leaf crinkle and leaf curl. The primary challenge in managing these viral diseases lies in effectively integrating the substantial knowledge accumulated, which is essential for developing genotypes with durable resistance to viral infections. Molecular markers and QTL (Quantitative Trait Locus) mapping are valuable tools for identifying genomic regions associated with viral disease resistance, aiding future breeding programs. This abstract provides an overview of each Vigna species, the viral diseases affecting them, and recent advancements in developing resistant genotypes. It also highlights systematic screening efforts within Vigna germplasm to identify various sources of viral resistance in Vigna species.